2015
DOI: 10.1111/caim.12110
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Knowledge, R&D Team Centrality and Radical Creativity

Abstract: The impact of team knowledge network structure on team creativity has seldom been explored. To address this gap, we argue that research and development (R&D) teams' radical creativity is not only associated with the source of diversified knowledge (insiders of the team, outsiders of the team and internet professional forums), but also with team knowledge network centrality. Data from 32 R&D teams in seven research institutions support our contention that diversified knowledge from all three sources positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 101 publications
1
42
1
5
Order By: Relevance
“…Two items ( α = 0.68) from Tang and Ye's () scale measured individual‐level acquired diversified knowledge (e.g., ‘The work‐related knowledge I get from my team is unique’). The variable was assessed on a 5‐point Likert scale ranging from ‘1’ (strongly disagree) to ‘5’ (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two items ( α = 0.68) from Tang and Ye's () scale measured individual‐level acquired diversified knowledge (e.g., ‘The work‐related knowledge I get from my team is unique’). The variable was assessed on a 5‐point Likert scale ranging from ‘1’ (strongly disagree) to ‘5’ (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…The generation of creative ideas is typically the result of the coming together of very different areas (Mumford and Gustafson, ). Research has found that diversified knowledge is positively associated with team radical creativity (Tang and Ye, ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations are increasingly willing to obtain and share information across organizational boundaries in order to facilitate innovation (e.g., Camelo, García, Sousa, & Valle, ; Ferreras‐Méndez, Newell, Fernández‐Mesa, & Alegre, ). External knowledge has been suggested to be especially important for exploration (Schultz, Schreyoegg, & von Reitzenstein, ; Tang & Ye, ), because communicating with diverse individuals brings diversified knowledge (Mannix & Neale, ). Exploration requires the development of new knowledge and not just learning how to use existing knowledge , and acquiring knowledge from external sources results in changes to schemas and the team's cognitive architecture (Perry‐Smith & Shalley, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The benefit of external knowledge searching can also be found in the technology development field. For example, in pharmaceutical firms, R&D employees' access to diversified external knowledge increased creativity (Tang, ) and knowledge sourcing behaviours foster R&D employee creativity (Khedhaouria, Montani, & Thurik, ). Similar results come from studies at the firm level.…”
Section: Literature Reviewmentioning
confidence: 99%